Land bridges : ancient environments, plant migrations, and New World connections - Graham, Alan, 1934- (The University of Chicago Press, 2018)
And conclusions. Events, processes, and responses ; Bering land bridge ; North Atlantic land bridge ; Antillean land bridge ; Central American land bridge ; Magellan land bridge -- Conceptual issues and future needs.